2021
DOI: 10.4187/respcare.08319
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics, Respiratory Mechanics, and Outcomes in Critically Ill Individuals With COVID-19 Infection in an Underserved Urban Population

Abstract: BACKGROUND:The COVID-19 outbreak in the United States has disproportionately affected Black individuals, but little is known about the factors that underlie this observation. Herein, we describe these associations with mortality in a largely minority underserved population. METHODS: This single-center retrospective observational study included all adult subjects with laboratory-confirmed SARS-Cov-2 treated in our ICU between March 15 and May 10, 2020. RESULTS: 128 critically ill adult subjects were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Thirty studies 7,19,24,25,27,[29][30][31][32][33]35,37,41,43,45,[48][49][50][51]53,59,60,62,63,[65][66][67][68][69]71,72 (58%) reported data on PaO2/FiO2. The median PaO2/FiO2 at admission ranged from 60 mmHg 44 to 442 mmHg 32 .…”
Section: Gas Exchange At Admissionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirty studies 7,19,24,25,27,[29][30][31][32][33]35,37,41,43,45,[48][49][50][51]53,59,60,62,63,[65][66][67][68][69]71,72 (58%) reported data on PaO2/FiO2. The median PaO2/FiO2 at admission ranged from 60 mmHg 44 to 442 mmHg 32 .…”
Section: Gas Exchange At Admissionmentioning
confidence: 99%
“…Excluding patients from the study by Ranzani et al, the proportion of patients treated with any support was 52%, and, of those, NIV and CPAP were comparably applied in 13.5% and 14.5% of patients, respectively. CPAP was administered in 11 studies (21.1%), and delivered generally by helmet 19,25,27,30,31,33,35,53 (8 studies, 72.7%), while in the remaining three studies the interface used was not reported 32,67,68 . In the study by Bellani et al 27 , the Authors report using the helmet CPAP in 68% of patients, while Vaschetto and colleagues 35 applied CPAP by helmet in 74%, by oro-nasal masks in 23% and by helmet/mask alternation in 3% of patients.…”
Section: Characteristics Of Respiratory Supportmentioning
confidence: 99%
See 3 more Smart Citations